Acute gastritis associated with Epstein-Barr virus infection in a child - Ji Mok Kim; Chun Woo Song; Kyu Sang Song; Jae Young Kim (Korean Pediatric Society, 2016)
Infectious mononucleosis is Epstein-Barr virus (EBV) inducing a self-limiting clinical syndrome characterized by fever, sore throat, hepatosplenomegaly, and generalized lymphadenopathy. Gastrointestinal symptoms of EBV infection are nonspecific and occur rarely. EBV inducing acute gastrointestinal pathology is poorly recognized without suspicion. Careful consideration is needed to diagnose gastric involvement of EBV infection including gastric lymphoma, gastric cancer, and gastritis. A few recent cases of gastritis associated with EBV infection have been reported in adolescents and adults. However, there is no report of EBV-associated gastritis in early childhood. We experienced a rare case of 4-year-old girl with EBV gastritis confirmed by in situ hybridization.